Meibomian gland dysfunction in Sjögren's disease - Anuwa-Amarh, Esther N.; Ziemanski, Jillian F. (Frontiers in Medicine, 2025)
For many years, lacrimal gland dysfunction was considered the primary cause of dry eye disease in Sjögren's Disease (SjD). However, recent studies reveal that meibomian gland dysfunction (MGD) is also a significant contributor in dry eye associated with SjD. Recent evidence shows severe meibomian gland damage, reduced tear lipid layer thickness, and abnormal tear evaporation rates, which could exacerbate dry eye symptoms in SjD. These findings challenge the traditional view of SjD dry eye as solely aqueous-deficiency and highlight the role of evaporative dry eye in SjD. While the exact mechanisms linking MGD to SjD remain unclear, researchers propose that inflammation, androgen deficiency, and neurological factors may play key roles. Despite these findings, there is limited research on targeted therapies for SjD-related MGD, which may contribute to why many SjD patients do not experience optimum relief with conventional treatments. This report examines the manifestation of MGD in SjD, explores potential pathophysiological mechanisms, and reviews current management strategies aimed at addressing SjD-related MGD, highlighting the need for further research to improve treatment outcomes.